مقاربة تاريخية وسياسية وحضارية في نتائج الاحتلالين الهكسوسي والكشي لمصر والعراق - الخفاجي، مزهر محسن; جابر، عادل شابث (جامعة عين شمس - كلية الآداب, 2018)
A Historical , Political and Cultural Approach In the Results of the Two Occupations Hyksos and Kassite of Egypt and Iraq By Adil Shabith Jabbir And Mizher Muhssin Al-Khafji It is undoubted that Hyksos and Kassite are considered as the foreign tribes that invaded Nile country and Mesopotamia between the seventeenth and sixteenth century BC. In spite of the various attitudes of the researchers about those tribes concerning the origin and nature of migration and geographic extension .but it is obvious that occupation has an effect on the historical, political , social and cultural aspects. This research is an attempt to trace these two occupation on the most important civilizations in the near east. In addition, it is an attempt to emphasize the idea of the rooting, geographical, historical and civilization of the those tribes. As well as, the cultural and historical results of this occupation on the nature of the cultural and historical achievements of the countries of the Nile and Mesopotamia.
يعد كل من الهكسوس والكاشيين، من الأقوام الأجنبية التي غزت كل من بلاد وادي النيل وبلاد الرافدين ما بين القرن السابع عشر والسادس عشر قبل الميلاد وإذا ما اقتنعنا باختلاف الباحثين في أصلهم وطبيعة هجرتها وتمددها الجغرافي وغرابة تعاصرهما الزماني، لكن المتفق عليه أن هذا الاحتلال قد ترك أثاراً على الأصعدة التاريخية السياسية والاجتماعية والحضارية. هذا البحث محاولة لاقتفاء أثر هذين الاحتلالين على أهم حضارتين في الشرق الأدنى، وهو محاولة أولية لتأصيل فكرة المشترك المكاني والجغرافي والتاريخي والحضارة لهذه الأقوام، ونتائج هذا الاحتلال الحضارية والتاريخية على طبيعة المنجز الحضاري والتاريخي لكل من بلاد النيل وبلاد الرافدين.
Keywords: الهكسوس -- الكاشيين -- بلاد وادى النيل -- بلاد الرافدين -- مصر -- العراق